Clumped-isotope-derived climate trends leading up to the end-Cretaceous mass extinction in northwestern Europe - H. E. O'Hora; S. V. Petersen; J. Vellekoop; M. M. Jones; S. R. Scholz (Climate of the Past, 2022)
Paleotemperature reconstructions of the end-Cretaceous interval document local and global climate trends, some driven by greenhouse gas emissions from Deccan Traps volcanism and associated feedbacks. Here, we present a new clumped-isotope-based paleotemperature record derived from fossil bivalves from the Maastrichtian type region in southeastern Netherlands and northeastern Belgium. Clumped isotope data document a mean temperature of 20.4±3.8 ∘ C, consistent with other Maastrichtian temperature estimates, and an average seawater δ 18 O value of 0.2±0.8 ‰ VSMOW for the region during the latest Cretaceous (67.1–66.0 Ma). A notable temperature increase at ∼66.4 Ma is interpreted to be a regional manifestation of the globally defined Late Maastrichtian Warming Event, linking Deccan Traps volcanic CO 2 emissions to climate change in the Maastricht region. Fluctuating seawater δ 18 O values coinciding with temperature changes suggest alternating influences of warm, salty southern-sourced waters and cooler, fresher northern-sourced waters from the Arctic Ocean. This new paleotemperature record contributes to the understanding of regional and global climate response to large-scale volcanism and ocean circulation changes leading up to a catastrophic mass extinction.